BOSHLANG‘ICH SINFDA O‘QISH SAVODXONLIGINI O‘RGATISHNING ZAMONAVIY USULLARI - Boltayeva, H. (SCIENCE and SOCIETY, 2025)
This article shows that reading literacy is not only the skills of students to work with text, but is also considered the basis of their general educational, personal and social development. Modern ways are shown to achieve reading literacy.
Keywords: education; text; motivation; collaborationism; communicativity